A Highly Sensitive Indirect Spectrophotometric Method for the Determination of Some Phenothiazine Drugs - Karimi, M.A.; Hormozi Nezhad, M.R. (Asian Journal of Chemistry, 2010)
A new, simple, rapid, sensitive and accurate indirect spectrophotometric method for the microdetermination of some phenothiazine drugs in pure form and pharmaceutical formulations is developed. The proposed method is based on the reaction of chlorpromazine hydrochloride (CPH), promethazine hydrochloride (PH), trifluoperazine hydrochloride (TFPH), trimipramine maleate (TPM) and thioridazine hydrochloride (TRDH) with copper(II) and a subsequent reaction with neocuproine (NC). In the presence of NC, Cu(II) is reduced easily by phenothiazine derivatives to Cu(I)-NC complex, which shows an absorption maximum at 450 om. The linearity ranges are found to be 0.3-150, 0.6-80, 0.5-190, 10-80 and 10-130 μg mL-1 for CPH, PH, TFPH, TPM and TRDH, respectively. This method was applied to the determination of these drugs in pharmaceutical formulations with recoveries in the range of 98.45-101.45%. The results obtained for the assay of pharmaceutical preparations compared well with those obtained by the official method and demonstrated good accuracy and precision.